Addressing the contribution of agricultural systems to the phosphorus pollution challenge: a multi-dimensional perspective - Martín-Hernández, Edgar; Taifouris, Manuel; Martín, Mariano (Frontiers in Chemical Engineering, 2022)
The intensification of agricultural systems has increased the food production efficiency, increasing the productivity while the production costs are reduced. Although these factors are key to global food security in a context of continued human population growth, the use of intensive agricultural techniques results in different environmental issues. Mitigating these negative impacts is a requirement for adopting sustainable food production systems. Notably, nutrient pollution is one of the main environmental issues associated with both livestock and crop production. These activities result in different point and non-point source releases of phosphorus, which eventually reach surface and ground waterbodies. This might result in the accumulation of phosphorus over time, contributing to the eutrophication of water ecosystems, and the development of harmful algal bloom (HABs) episodes. The releases of nutrients from agricultural activities can be abated through different management strategies, including the implementation of nutrient recovery techniques at livestock facilities, embracing precision fertilization methods, and developing integrated crop-livestock systems for achieving circular food production systems. In this work, we describe opportunities for Process System Engineering (PSE) to address the development of phosphorus management techniques for mitigating phosphorus pollution from agricultural systems balancing trade-offs between recovery cost and environmental impact mitigation. These techniques integrate the spatial analysis of nutrient pollution from agriculture using geographical information systems (GIS) with the assessment and the selection of phosphorus management techniques combining techno-economic analysis (TEA) and environmental metrics through multi-criteria decision analysis (MCDA) frameworks, and use mathematical programming for the conceptual design of integrated crop-livestock systems.